Effects of empowerment and engagement on performance in the Chilean textile industry employees - Juyumaya, Jesus Enrique; Alvarado, Nicole; Rojas, Carolina (Estudios de Administración, 2021)
This research studies how work engagement achieved through psychological empowerment can improve on-the-job performance of employees in the Chilean textile industry. A mediation model is suggested that analyzes work engagement as a mediator in the direct relationship between psychological empowerment and job performance. Findings indicate that an employee will indeed perform better if she/he is psychologically empowered to manage her or his own skills when tackling a task. In effect, engaging the employee with the task, itself will have even more positive repercussions on performance. The study provides empirical evidence for understanding work engagement in Latin American contexts, apart from its practical implications for managing workforce in Chile’s textile industry.